1967
DOI: 10.1002/prop.19670150202
|View full text |Cite
|
Sign up to set email alerts
|

Die Höhen‐ und Zenitwinkelabhängigkeit der Energiespektren von Ultrastrahlungsteilchen

Abstract: ZusammenfassungDie Energiespektren der kosmischen Strahlung sind von zweifacher Bedeutung. Einmal stellen sie eine wichtige ,,Konstante" der kosmischen Strahlung dar, zum andern lassen sich durch Vergleich der Spektren in verschiedenen Hohenbereichen der Atmosphare Ruckschlusse auf die Wechselwirkungsprozesse ableiten, die beim Weg der Ultrastrahlung durch die Atmosphare statthden. Die gangigen apparativen Methoden reichen zwar im allgemeinen aus, Energiespektren auf Meereshohe zu untersuchen, sie sind jedoch … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1995
1995
2006
2006

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 67 publications
0
1
0
Order By: Relevance
“…The data for constructing the functions ) , 0 ( p j and ) ( p n can be found in the literature (Allkofer et al, 1967(Allkofer et al, , 1971(Allkofer et al, , 1975(Allkofer et al, , 1984Moroney and Parry, 1954). It was shown that finer dependencies such as the EastWest muon flux asymmetry, the dependence of the muon charge ratio on the muon momentum, latitudinal and seasonal variations can be neglected (Vojtyla, 1995).…”
Section: Surface Laboratoriesmentioning
confidence: 99%
“…The data for constructing the functions ) , 0 ( p j and ) ( p n can be found in the literature (Allkofer et al, 1967(Allkofer et al, , 1971(Allkofer et al, , 1975(Allkofer et al, , 1984Moroney and Parry, 1954). It was shown that finer dependencies such as the EastWest muon flux asymmetry, the dependence of the muon charge ratio on the muon momentum, latitudinal and seasonal variations can be neglected (Vojtyla, 1995).…”
Section: Surface Laboratoriesmentioning
confidence: 99%